Unearthing the political unconscious in the reporting of homelessness in Manchester. (1st March 2020) - Broady, Rachel
Journalists in Manchester have reported on homelessness with the intention of highlighting a problem, persuading a charitable response and encouraging legislative intervention. They serve as the way for readers, who may not spend time among the homeless, to observe and understand. This article argues that the representation is restricted by the ideological arena in which journalists work. It posits that by utilizing Fredric Jameson's interpretive horizons methodology, the political unconscious of copy can be unearthed to reveal the acceptance of the inevitability of homelessness, which has been internalized and reconfigured in stories about the topic. It argues that it is possible to reveal the strategies of containment unconsciously employed, which conceal the relationship between labour and value, and ultimately defend the status quo, despite the intentions of journalists and publications. It further posits that the systemic, societal causes of homelessness are ultimately unchallenged, with the experience unconsciously mediated by the journalists and shared with an audience treated as fellow observers.